2010
DOI: 10.1111/j.1601-183x.2009.00545.x
|View full text |Cite
|
Sign up to set email alerts
|

Isoform‐specific effects of apolipoprotein E on cognitive performance in targeted‐replacement mice overexpressing human APP

Abstract: The ε4 allele of apolipoprotein E (apoE4) is the predominant genetic risk factor for late-onset Alzheimer's disease (AD) and is also implicated in cognitive deficits associated with normal aging. The biological mechanisms by which APOE genotype affects cognitive processes or AD pathogenesis remain unclear, but interactions of apoE with amyloid β peptide (Aβ) are thought to play an important role in mediating apoE's isoformspecific effects on brain function. Here, we investigated the potential isoform-dependent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 52 publications
3
14
1
Order By: Relevance
“…The study revealed that the performance of the apoE4 mice in the object recognition and Morris water maze was impaired relative to that of the apoE3 mice and that it was also impaired in the contextual but not in the cued fear conditioning response.These findings are in accordance with previous results obtained utilizing a dry version of the Morris water maze and fear conditioning test results, which were obtained using young apoE4 mice [23,30]. They also extend previous studies that revealed that adult apoE4 mice are cognitively impaired [32,34,36,37,41,42,43,44] and suggest that, like in humans, the apoE4-driven cognitive impairments begin early in life [45,46]. …”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…The study revealed that the performance of the apoE4 mice in the object recognition and Morris water maze was impaired relative to that of the apoE3 mice and that it was also impaired in the contextual but not in the cued fear conditioning response.These findings are in accordance with previous results obtained utilizing a dry version of the Morris water maze and fear conditioning test results, which were obtained using young apoE4 mice [23,30]. They also extend previous studies that revealed that adult apoE4 mice are cognitively impaired [32,34,36,37,41,42,43,44] and suggest that, like in humans, the apoE4-driven cognitive impairments begin early in life [45,46]. …”
Section: Discussionsupporting
confidence: 82%
“…On day 3, the mice were placed in the original conditioning chamber (context A) and kept there for 300 s without either the tone or the foot shock. The freezing behavior of the mice, which is an indication of fear memory, was recorded and analyzed utilizing the FreezFrame 3.0 video tracking software system and the FreezView software system [29,31,32,33]. …”
Section: Methodsmentioning
confidence: 99%
“…Both groups showed similar velocities throughout testing and performed similarly well in the visible-platform task, suggesting that differences in hidden-platform performance were not related to differences in sensory-motor abilities or other confounding factors like motivation. Similarly to what was found in older hAPP-Yac/apoE female mice [19] in different settings, hAPP-Yac/apoE4-TR male mice were slightly less active than hAPP-Yac/apoE3-TR mice during the first hour spent in a new environment and during the 21 h session after habituation to the activity device. Interestingly, hAPP-Yac/apoE4-TR mice were also less active during the free swim habituation trial, but not during subsequent water-maze training.…”
Section: Introductionsupporting
confidence: 76%
“…Since human APP and apoE genes differ from their respective homologues in mice, these bigenic mice provide an interesting tool to study specific in vivo interactions between human apoE isoforms and APP at the behavioral level. Interestingly, spatial memory performances are preserved in 4.5-9 months old single transgenic hAPP-YAC mice [20], whereas the bigenic hAPP-Yac/apoE4-TR female mice, but not males, showed some early deficits in spatial memory, fear conditioning and attentional tasks compared to hAPP/apoE3-TR mice at the age of 6-7 months [19,21]. The cognitive status of younger hAPP-Yac/apoE-TR mice is still unknown.…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation